Injury, Training, Biomechanical, and Physiological Profiles of Professional Breakdancers - Amelia J.H. Arundale; Roisin McNulty; Cory Snyder; James O'Brien; Thomas Stöggl (International Journal of Sports Physical Therapy)
# Background